Bioinformatic prediction of immunodominant regions in spike protein for early diagnosis of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) - Zhuang,Siqi; Tang,Lingli; Dai,Yufeng; Feng,Xiaojing; Fang,Yiyuan; Tang,Haoneng; Jiang,Ping; Wu,Xiang; Fang,Hezhi; Chen,Hongzhi (PeerJ, 2021)
Background To contain the pandemics caused by SARS-CoV-2, early detection approaches with high accuracy and accessibility are critical. Generating an antigen-capture based detection system would be an ideal strategy complementing the current methods based on nucleic acids and antibody detection. The spike protein is found on the outside of virus particles and appropriate for antigen detection. Methods In this study, we utilized bioinformatics approaches to explore the immunodominant fragments on spike protein of SARS-CoV-2. Results The S1 subunit of spike protein was identified with higher sequence specificity. Three immunodominant fragments, Spike56-94, Spike199-264, and Spike577-612, located at the S1 subunit were finally selected via bioinformatics analysis. The glycosylation sites and high-frequency mutation sites on spike protein were circumvented in the antigen design. All the identified fragments present qualified antigenicity, hydrophilicity, and surface accessibility. A recombinant antigen with a length of 194 amino acids (aa) consisting of the selected immunodominant fragments as well as a universal Th epitope was finally constructed. Conclusion The recombinant peptide encoded by the construct contains multiple immunodominant epitopes, which is expected to stimulate a strong immune response in mice and generate qualified antibodies for SARS-CoV-2 detection.
Keywords: SARS-CoV-2; Spike protein; Antigen-capture; Immunodominant fragments; COVID-19